Penerapan Algoritma K-Nearest Neighbor Dalam Menentukan Kualitas Buah Jeruk Bali - Musbar Fandi Harahap; Fera Damayanti; Siti Sundari (Jurnal Informatika, 2024)
Grapefruit, large orange or pomelo (Citrus maxima) could be a native Indonesian fruit plant that has high economic value. Grapefruit is spread across various regions in Indonesia and has various types of fruit such as Bali Merah, Cikoneng, Nambangan, Raja, Ratu, and Pangkep. Grapefruit (Citrus maxima) is one of three types of local citrus besides Citrus medica and Citrus reticulate. Grapefruit grows in tropical areas so that grapefruit has the potential to be cultivated in Indonesia. The quality of grapefruit is usually obtained through selection by distinguishing contrast based on the characteristics of natural materials, calculating the dosage and shape of natural materials, the shape of the tip and base of natural materials, the color and surface of grapefruit fruit. flavedo (epicarp), viscosity and color of albedo (mesocarp), color of endocarp, color and taste of vesicles or natural product tissue, odor of essential oils, number of natural products per tree and number of seeds in each natural product. Test results using the grapefruit application in data mining processing using KNN calculations. In the data testing, the precision value was obtained:0.834, Classification precision:0.860, F1:0.860, accuracy:0.861, review:0.860 and MCC:0.720 on the test data.